The Relationship between Experiential Marketing and Determinants of Quality Service in the Banking Market - Oliveira, Dayane (2020)
The purpose of this manuscript is to analyze the relationship between experiential marketing and some of the determinants of loyalty in the banking market. The banking market has undergone a number of changes due to growing competitiveness, advancing technologies and increasing consumer choice, influence and intervention, making it necessary to focus on new marketing strategies designed to create profitable, long-term relationships that target consumer loyalty. With regard to the methodology, a descriptive research with a quantitative approach was chosen. Data collection was performed through the application of an online questionnaire to a non-probabilistic convenience sample, reaching 211 valid answers. The main results point to the existence of a relationship between the participation in experiences (experiential marketing) and some of the determinants of loyalty, highlighting the experiences related to technology, the bank's agency internal environment and product and service experimentation for a certain time at no charge. From an interdisciplinary perspective, this manuscript presents contributions to banking management and marketing. The work proposed here is expected to be an aid instrument for a further promotion of loyalty. Experiential marketing can be a strategy that leads to greater loyalty in the banking market.